First record of the leech, Glossiphonia complanata (Linnaeus, 1758) infection in freshwater pearl mussel Lamellidens marginalis (Lamarck, 1819) - Paul, A.; Pattanayak, S.; Pradhan, S.; Saurabh, S.; Sahoo, P. K. (Indian Journal of Fisheries, 2018)
Demand and production of freshwater pearl mussel Lamellidens marginalis (Lamarck, 1819) have increased many folds in the last few decades. There are only very scanty reports of infective agents and their pathogenicity affecting this particular mussel species. Heavy infestation and mortality of L. marginalis were observed in the ponds of Freshwater Pearl Mussel Unit of ICAR-Central Institute of Freshwater Aquaculture (ICAR-CIFA), Bhubaneswar during April, 2017. All (100%) of the pond collected pearl mussels were infected with leeches both on outside as well as internal parts of the shell at 5-20 numbers per mussel. The infected mussels showed low surgical success rate for pearl production. Mortality to the tune of 30% was recorded in the tanks of 35 l capacity stocked with 10 numbers of mussels. The infectious leech was identified as Glossiphonia complanata by 28S rDNA PCR followed by sequencing and phylogenetic analysis. The present communication is the first report on G. complanata causing mortality in L. marginalis farming.